Against the odds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In The Gambia?s Kombo district land-grabbing for settlement is the norm. However, one community has stood against this, asserting their traditional rights to their forest, and carrying out extensive conservation work to preserve it for future generations.